Modelling and Numerics for Respiratory Aerosols (Communications in Computational Physics, 2018)
In this work, we present a model for an aerosol (air/particle mixture) in therespiratory system. It consists of the incompressible Navier-Stokes equations for theair and the Vlasov equation for the particles in a fixed or moving domain, coupledthrough a drag force. We propose a discretization of the model, investigate stabilityproperties of the numerical code and sensitivity to parameter perturbation. We alsofocus on the influence of the aerosol on the airflow.